Efektivitas Terapi Foot Massage Dalam Mengurangi Nyeri Pada Pasien Post-Histerektomi Dengan Mioma Uteri - Vidya Ananda; Sri Sumaryani; Eny Hernani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Foot massage therapy is a technique that uses patting, stroking, or pressure to distract and divert connective tissue to increase foot muscle tone, improve circulation, and induce relaxation, by releasing endorphins, it can also increase the pain threshold. The purpose of this study was to evaluate the effectiveness of foot massage therapy in reducing pain in post-hysterectomy patients with uterine myoma. This study uses a descriptive design with a case study approach to nursing care for 3 days with a foot massage therapy intervention for 15 minutes to case study subjects who are evaluated using the Numeric Rating Scale. This case study was conducted at Muhammadiyah PKU Gamping Hospital Yogyakarta on May 8-10, 2024. The results of the intervention evaluation from the first day to the third day showed that patients reported a decrease in pain from a scale of 9 to a scale of 4 after being given foot massage therapy. This decrease in pain level is not only the effect of foot massage therapy alone, but also from the medications taken during treatment. In addition to reducing pain, this therapy can also make patients more comfortable and relaxed.